1978
DOI: 10.1136/jcp.31.7.659
|View full text |Cite
|
Sign up to set email alerts
|

Specific and non-specific folate binding protein in normal and malignant human tissues

Abstract: Binding of tritiated folic acid by supernatants prepared from extracts of normal and leukaemic leucocytes, normal mucosa, and malignant tumours from different parts of the gastrointestinal tract has been measured using Sephadex-gel filtration and albumin-coated charcoal techniques. Non-specific binding (measured by Sephadex G-75 gel filtration) was almost invariably greater than specific binding measured by albumin-coated charcoal separation of bound and unbound folate. In nine normal leucocyte extracts, bindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

1980
1980
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…These results show that human LPM are able to bind labelled folic acid, confirming previous data [6,22], Since folate binding proteins are also present inside liver cells [7] purity of the membrane preparation was essential for this study. The absence of G-6-PD and SD from the LPM and other membrane preparations and the absence of other cellular organelles, including leuko cyte granules on light microscopy, excluded the possibility that binding detected here was due to cytoplasmic contamination.…”
Section: Discussionsupporting
confidence: 79%
“…These results show that human LPM are able to bind labelled folic acid, confirming previous data [6,22], Since folate binding proteins are also present inside liver cells [7] purity of the membrane preparation was essential for this study. The absence of G-6-PD and SD from the LPM and other membrane preparations and the absence of other cellular organelles, including leuko cyte granules on light microscopy, excluded the possibility that binding detected here was due to cytoplasmic contamination.…”
Section: Discussionsupporting
confidence: 79%
“…A corollary of this model is that if a weak interaction occurs between the osmolytes and DHF and/or folate, then perhaps folate and/or DHF may bind to various proteins and/or cellular components. Some support for this corollary comes from various examples of nonspecific folate binding to proteins as well as specific binding of folate to the central cavity in hemoglobin . Also, the Record group has experimentally found that betaine can compete with water and interact with amide and cationic nitrogens as well as aromatic hydrocarbons in small molecules .…”
Section: Discussionmentioning
confidence: 99%
“…In an extension of our model, we ask if it is possible that folate may bind to various macromolecules. Other examples of weak binding of folate to various proteins have been noted. Also, folate has been crystallized in the central cavity of hemoglobin . Most recently, a mass spectroscopy “allosterome” approach has searched for metabolite–protein interactions and found that folate inhibits glutamate dehydrogenase, glucose-6-phosphate dehydrogenase, and NAD kinase .…”
Section: Discussionmentioning
confidence: 99%